JOB BURNOUT OF TEACHERS – PRESENTATION OF CHOSEN CONCEPTIONS AND RESEARCHES - Agnieszka Rowicka; Iwona Błaszczak (Studia z Teorii Wychowania)
Nowadays job burnout is concerned to be a serious problem not only in the individual but also in the social dimension. Extensive researches point out that it is a common and, at the same time, strongly escalating issue, which in particular concerns representatives of social services’ workers. Especially affected are teachers, doctors, nurses, police people, rescue workers, psychotherapist, so the ones who are professionally involved with commitment to another ones and close interaction with them. Undoubtedly such kind of job could become a source of satisfaction and fulfilment, however, at the same time, itexposes to bearing high psychological charges, especially in the situations connected with high expectations, going beyond one’s possibilities. In this article, given the burning issue, which isteachers’ job burnout in modern education, the author presented key theoretical conceptions and empirical researches of prominent representatives who work on this topic.